PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KOMITMEN PEGAWAI PT. LINTANG SARANA MEDIA MALANG - Apriyanti, Apriyanti (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2016)
Attention to Human Resources within an organization is critical to gaining employee commitment as expected. Employee commitment itself is influenced by many factors, including compensation and job satisfaction. This study aims to analyze the influence of Compensation and Job Satisfaction. This study aims to clarify the effect of compensation and job satisfaction to employee commitment to the organization. Compensation should be able to trigger the desired behavior in organizations such good performance, loyalty and responsibility on organizational commitment. While job satisfaction is the compatibility between one's expectations that arise in return provided by the job. So if the company can provide appropriate compensation and employee expectations employee satisfaction with the job may have given the company, the employee will have a high level of commitment to the work place. The population of this research is all the administrative staff of: PT.Lintang Sarana Media Malang The sampling technique used is total sampling with a sample of 40 people. Collecting the results was conducted by questionnaire and the results were analyzed using multiple linear regression analysis.